Sovereign Marketing: A New Strategy of Marketing - Ahmed, Gouher (Scientific Research, 2017)
The importance of “sovereign” consumerism is well established in business and marketing theory. It is a familiar business saying that the consumer is the king of the market or market king, which is truer in theory rather than in realty. But this myth appears to be turning into reality with the rise of free market philosophy, all over and the consequent intense competition at home and abroad, which, the father of business science, Adam Smith presumed to be most conducive for the growth of national wealth and welfare. Sovereign marketing (SM) is the new strategy of consumer oriented marketing intended to give the new and best deal through the new and multiple feature commodities, etc., which form the thrust of this paper. It is to highlight this changing marketing scenario with the help of new marketing methodologies of high advertisement and 24/7/365 direct marketing, which indicate the consumer getting the best deal in the new 21st century marketing from which sovereign marketing found to be the best marketing type for social good.
Keywords: Sovereign Marketing; 21st Century Marketing; Consumer Oriented Marketing Strategy; Indian Marketing Dynamics; Marketing Deal; Emerging Market